Repression of the B cell identity factor Pax5 is not required for plasma cell development - Liu, Grace J.; Jaritz, Markus; Wöhner, Miriam; Agerer, Benedikt; Bergthaler, Andreas; Malin, Stephen G.; Busslinger, Meinrad (Journal of Experimental Medicine, 2020)
B cell and plasma cell fates are controlled by different transcriptional networks, as exemplified by the mutually exclusive expression and cross-antagonism of the B cell identity factor Pax5 and the plasma cell regulator Blimp1. It has been postulated that repression of Pax5 by Blimp1 is essential for plasma cell development. Here, we challenged this hypothesis by analyzing the IghPax5/+ mouse, which expressed a Pax5 minigene from the immunoglobulin heavy-chain locus. Despite high Pax5 expression, plasma cells efficiently developed in young IghPax5/+ mice at steady state and upon immunization, while their number moderately declined in older mice. Although Pax5 significantly deregulated the plasma cell expression program, key plasma cell regulators were normally expressed in IghPax5/+ plasma cells. While IgM and IgA secretion by IghPax5/+ plasma cells was normal, IgG secretion was modestly decreased. Hence, Pax5 repression is not essential for robust plasma cell development and antibody secretion, although it is required for optimal IgG production and accumulation of long-lived plasma cells.
Created from Fastlane, Scopus look-up